Motive-Modulated Attentional Orienting: Implicit Power Motive Predicts Attentional Avoidance of Signals of Interpersonal Dominance - Janson, Kevin; Köllner, Martin; Khalaidovski, Ksenia; Pülschen, Lea Sarah; Rudnaya, Alexandra; Stamm, Laura; Schultheiss, Oliver (Motivation Science, 2021)
Implicit motives are commonly believed to orient behavior. Despite only sparse empirical evidence for this claim, an interplay of implicit motives and the attentional system seems plausible. In 2 preregistered eye-tracking studies (total N = 263 after exclusions), we tested whether the implicit power motive (nPower), the capacity to derive pleasure from having impact on others, measured via the Picture Story Exercise, predicted participants’ attentional orienting. Participants were simultaneously presented neutral faces and facial expressions of emotion (FEEs), with the latter signaling either dominance or submission. In both studies, nPower predicted initial avoidance of anger FEEs, which were deemed to be an aversive dominance signal. Initial orienting toward submissive FEEs was not predicted significantly by nPower. Results are discussed in the light of recent findings in neuroscience and with reference to limitations of our design. Our findings suggest that implicit motives do have an orienting function regarding initial responses to the encounter of interpersonal dominance signals.
CRIS-Team Scopus Importer:2021-12-17
Keywords: attentional orienting; eye-tracking; facial expressions of emotion; implicit motives; need for power

The Ulna-to-Fibula Ratio as a Marker of Organizational Hormone Effects on Implicit Motive Development: A High-Powered Preregistered Replication - Köllner, Martin; Puelschen, Lea-Sarah; Stamm, Laura; Janson, Kevin (Motivation Science, 2022)
This preregistered study (N = 250; 148 women; after exclusions) aimed at replicating findings by Kollner and Bleck (2020) regarding relationships of the implicit power motive (nPower) and activity inhibition with their proposed new marker of pubertal organizational hormone effects, the ulna-to-fibula ratio (UFR). Our cross-sectional design included the Picture-Story Exercise (nPower, activity inhibition) and anthropometry of ulna and fibula length, facial width and height, shoulder/waist/hip circumference, and 2D:4D digit ratio. As a validation check for organizational hormone effects' relationships to motivation, we tested UFR's sex-dimorphism, independence of body height, and interrelationships with other markers. Results showed that the validation check was successful. UFR was sex-dimorphic, independent of body height, and significantly associated with other possible markers of pubertal organizational hormone effects, including facial width-to-height ratio, waist-to-hip ratio, and shoulder-to-hip ratio. As predicted, a "sex-typical" UFR, low for women and high for men, was associated with the inhibited power motive (outliers excluded). nPower's sex-dimorphic relationship with UFR reported by Kollner and Bleck (2020) was not replicated. UFR's relationship with the inhibited power motive, in conjunction with findings by Schultheiss et al. (2019) for prenatal organizational hormone effects, add to accumulating first evidence for hormonal contributions to implicit motive development but also call for larger-sample replication.
CRIS-Team WoS Importer:2022-07-01